2019
DOI: 10.1002/smll.201901919
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Mechanically Robust Metal‐Based Water Repellent Surface Enabled by Scalable Construction of a Flexible Coral‐Reef‐Like Architecture

Abstract: Mechanical robustness is a central concern for moving artificial superhydrophobic surfaces to application practices. It is believed that bulk hydrophilic materials cannot be use to construct micro/nanoarchitectures for superhydrophobicity since abrasion‐induced exposure of hydrophilic surfaces leads to remarkable degradation of water repellency. To address this challenge, the robust mechanical durability of a superhydrophobic surface with metal (hydrophilic) textures, through scalable construction of a flexibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…
Fig. 21 The water repellency of cold sprayed Cu-based superhydrophobic coating: (a) the superhydrophobic performance on different substrate materials including (a1) Al alloy, (a2) Mg Alloy, (a3) Al2O3 ceramic and (a4) optical glass; (b) the results of water contact angle and water sliding angle on different substrates; (c) self-cleaning test result by using sticky starch powders; (d) the enhanced floating ability of different plates with superhydrophobic coating (Ref 244 )
…”
Section: Cold Spray Application Pillars (Past Present and Future)mentioning
confidence: 99%
“…
Fig. 21 The water repellency of cold sprayed Cu-based superhydrophobic coating: (a) the superhydrophobic performance on different substrate materials including (a1) Al alloy, (a2) Mg Alloy, (a3) Al2O3 ceramic and (a4) optical glass; (b) the results of water contact angle and water sliding angle on different substrates; (c) self-cleaning test result by using sticky starch powders; (d) the enhanced floating ability of different plates with superhydrophobic coating (Ref 244 )
…”
Section: Cold Spray Application Pillars (Past Present and Future)mentioning
confidence: 99%
“…The wettability of the coatings prepared was evaluated by water contact angle measurements on a video-based optical system (Kino SL200B), five readings were achieved for each sample. The mechanical robustness of the superhydrophobic surface was assessed by both sandpaper and sand particle abrasion tests 46 , 47 . For the sandpaper abrasion experiments, the coating surface was placed onto 80# mesh sandpaper with a constant load of 100 g and slowly moved at a speed of 5 cm/s for 15 cm along both the horizontal and vertical directions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is worth to note that the roughness of superhydrophobic surface should be optimized in the process of preparing superhydrophobic surface to improve its mechanical robustness. Luo et al reported a superhydrophobic surface which has the robust mechanical durability because of the flexible coral-reeflike hierarchical structure [52] (figure 6). The durability of hierarchical architectures is attributed to the flexible coralreef-like structure constructed by kinetic spray process.…”
Section: Durable Superhydrophobic Light Alloy Materials 31 Robust Superhydrophobic Light Alloy Materialsmentioning
confidence: 99%
“…Figure 6. Superhydrophobic surface with a flexible hierarchical rough structure[52] : The surface topography of the flame-oxidized coating (a) and enlarged(b). (c) Superhydrophobicity on various substrates.…”
mentioning
confidence: 99%